Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(=\left(x^2+3x+1\right)^2-2\left(x^2+3x+1\right)\left(3x-1\right)+\left(3x-1\right)^2\)
\(=\left(x^2+3x+1-3x+1\right)^2\)
\(=\left(x^2+2\right)^2\)
b) \(=\left[\left(3x^3+1\right)^2-\left(3x\right)^2\right]-\left(3x^2+1\right)^2\)
\(=-\left(3x\right)^2=9x^2\)
c)\(=\left[\left(2x^2+1\right)^2-\left(2x\right)^2\right]-\left(2x^2+1\right)^2\)
\(=-\left(2x\right)^2=4x^2\)
(2x+1)2+(2x-1)2-2(4x2-1)
= (4x2+2x+1)+(4x2-2x+1)-8x2+2
= 4x2+2x+1+4x2-2x+1-8x2+2
= 1+1+2
= 4
(2x+1)2 + (2x-1)2 - 2(4x2-1)
= (2x+1)2 + (2x-1)2 - 2[(2x)2-1]
= (2x+1)2 + (2x-1)2 - 2(2x+1)(2x-1)
= (2x+1-2x+1)2
= 22
= 4
\(\left(2x+1\right)^2+\left(2x-1\right)^2-2\left(1-4x^2\right)\)
\(=\left(4x^2+4x+1\right)+\left(4x^2-4x+1\right)-\left(2-8x^2\right)\)
\(=4x^2+4x+1+4x^2-4x+1-2+8x^2\)
\(=16x^2\)
Lời giải:
$(2x+1)^2+2x(4x^2-1)+(2x-1)^2=4x^2+4x+1+8x^3-2x+4x^2-4x+1$
$=8x^3+(4x^2+4x^2)+(4x-2x-4x)+(1+1)=8x^3+8x^2-2x+2$